Monoclonal antibodies to human urokinase identify the single-chain pro-urokinase precursor. - Salerno, G (1984)
Monoclonal antibodies have been obtained that recognize either the A or B chain of human urinary urokinase. These antibodies identify human urokinase-producing cells and the product of urokinase mRNA. Anti-urokinase monoclonal antibodies precipitate an approximately equal to 54,000-dalton protein synthesized in vitro in a rabbit reticulocyte cell-free system. This pro-urokinase appears to be the precursor of both A and B chains of human urinary urokinase. Urokinase mRNA in human kidney constitutes only 0.1% or less of total poly(A)+ RNA.